Pain self‐management plus nurse‐led support in young adults with irritable bowel syndrome: Study protocol for a pilot randomized control trial. Issue 2 (1st February 2018) - Cong, Xiaomei; Ramesh, Divya; Perry, Mallory; Xu, Wanli; Bernier, Katherine M.; Young, Erin E.; Walsh, Stephen; Starkweather, Angela
ABSTRACT: Irritable bowel syndrome (IBS) is a functional gut disorder that typically manifests in early adult years. IBS patients report that pain is the most distressing symptom with the greatest impact on quality of life. Pain‐sensitivity genes and the gut microbiome may influence severity of symptoms as well as response to self‐management (SM) interventions. Based on current understanding of the science of SM, pain neurophysiology, and the gut‐brain axis, our team developed a pain SM intervention to be added to evidence‐based self‐management instruction to increase the individual's SM knowledge and skills (self‐efficacy, self‐regulation, and goal‐setting). The purpose of this randomized controlled longitudinal pilot study is to examine the feasibility, acceptability, and preliminary effectiveness of the IBS‐pain SM intervention on IBS‐pain SM behaviors and related health outcomes. A sample of 80 young adults (age 18–29 years old) will be recruited and randomly assigned to the experimental or control group. Both groups will receive 10 electronic video modules focused on IBS‐pain SM knowledge and skills. The experimental group also will receive nurse‐led one‐on‐one phone consultations to facilitate monitoring and problem‐solving. All participants will be followed over 12 weeks. Primary outcomes will be measured at baseline, 6 weeks, and 12 weeks, including IBS‐pain SM behaviors, quality of life, and well‐being. The influence of pain‐sensitivity genes and the gut microbiome on IBS‐pain SM behaviors and health outcomes also will be assessed.